Corruption and international trade: A re-assessment with intra-national flows - Silviano Esteve Pérez; Salvador Gil-Pareja; Rafael Llorca-Vivero; Jordi Paniagua (Economics: The Open-Access, Open-Assessment Journal, 2021)
This study re-examines the impact of corruption on international trade accounting for both inter- and intra-national flows in line with the latest advances in the gravity equation literature. Using a wide sample of countries for the period 1995-2017, our results show that the non-inclusion of internal trade flows drastically biases the estimations. Additionally, we find that the negative impact of corruption on trade is reduced, ceteris paribus, in poorer countries. We also find non-linearities, more corrupt countries present a more harmful impact of corruption on trade. Moreover, we perform a general equilibrium analysis to investigate the impact of a given reduction in perceived corruption on a selected group of countries' economic growth and prices. We find that these effects are far from being negligible, especially when there is a "synchronized" reduction in corruption in most corrupt countries.
Keywords: 330; corruption; general equilibrium; gravity; intra-national trade flows